Study Of Physiochemical Characteristics Of EFB Briquettes And Its Potential Use As Dual Feul In Cvcc - Nasir, Md Khidir Amin Md (Universiti Sains Malaysia, 2019)
Empty fruit bunch (EFB) briquette has become a potential plantation wastes to be converted into alternative gaseous fuel via combustion of its briquettes. EFB briquetting is referring to compacting biomass such as EFB into high density solid form. Many researchers found that using binder will improve the elastic condition and plastic deformation of EFB briquette. However, there is still a lot of opportunities in exploring a better formula between EFB to binder ratio. The aims of this study are to improve physical and chemical properties of EFB briquette through characterization of briquetting method and binder composition. and to test the EFB briquettes in downdraft type gasifier for the production of biomass producer gas. The biomass producer gas from EFB briquettes gasification was cleaned, compressed and stored in the gas tank for its spraying and combustion characteristics study. Based on this study, the potential of biomass producer gas as an alternative gaseous fuel for engine application was determined. Downdraft gasifier was chosen in this study due to the advantage of this gasifier in producing a low tar content in the production of biomass producer gas. Producer gas will be tested via open burning test in order to determine the spraying and combustion of producer gas of EFB briquette is comparable to commercial gaseous fuel such as Liquefied Petroleum Gas (LPG) and NGV. In the application of gaseous fuel in internal combustion engine, the tar content must be significantly low which is approximately 50-100 mg/Nm3. In summary, Mechanical strength of carbonized EFB briquettes improved four times higher as binder at the formulation of tapioca starch. Its calorific value improved from 36% compared with previous EFB briquettes. The flame propagation of biomass producer gas was comparable to the flame propagation of LPG and NGV via open burning test. With the aid of diesel fuel during startup, the flash point of biomass producer gas was at 360 deg. C.